PCA APPLICATION TO OBTAIN CHARACTER SELECTION MARKERS OF LOW NITROGEN TOLERANT HYBRID MAIZE - Priyanto, Slamet Bambang; Suwarti, Suwarti; Syahruddin, Karlina; Efendi, Roy (Jurnal Agrotek Tropika, 2025)
Using secondary characters for indirect selection can increase the efficiency of selecting maize yield at Low Nitrogen (N) conditions. This study aimed to investigate secondary characteristics that can be applied in the indirect selection of maize yield at Low N conditions. Thirty-nine maize genotypes were arranged in a split plot design with two replications at Bajeng Experimental Farm of Indonesian Cereal Research Institute from August to December 2019. Three Nitrogen fertilizers (0 kg N ha-1, 100 kg N ha-1, 200 kg N ha-1) as the main plot and maize genotype as a subplot. The observed variables were agronomic traits and yield component traits. Principal Component Analysis and correlation were used to determine traits for yield maize indirect selection at Low N. The results showed that plant height, ear height, days to anthesis, days to silking, ear diameter, seed number per row, harvested weight, shelling percentage, and Harvest Index were secondary characters that could be used as the indirect selection in low Nitrogen tolerance.